The baroque definition of the real in Descartes in light of Suárezian metaphysics - Barroso Fernández, Óscar (Anales del Seminario de Historia de la Filosofía, 2022)
The aim of this paper is to analyse the different meanings of the word “reality” in the work of Descartes. As a methodological strategy, a comparison with the conceptualization of the real in the work of Francisco Suárez is made. It makes possible to find a paradoxical tension between two conceptions of the real, the objective and the existential, in the work of both authors. It is argued that this tension is a typical character of the metaphysics in the baroque period, better resolved by Descartes than by Suárez thanks to the theological foundation of knowledge proposed by the first. This foundation ensures the correspondence of the true ideas, known a priori, with extramental reality and it hinders the phenomenological and pre-Kantian interpretation of the cartesian ontology in terms of reduction of reality to realitas objectiva.
Keywords: Descartes; existence; objectivity; baroque metaphysics; reality; Suárez